People with schizophrenia can become resilient while recovering - Liersch, Susan; Curtis, Janette; Caputi, Peter (Développement Humain, Handicap et Changement Social / Human Development, Disability, and Social Change)

(untitled) (Réseau International sur le Processus de Production du Handicap, 2011)
People diagnosed with schizophrenia who consider themselves to have recovered were interviewed to identify what they believe resilience is and how it may have been involved in their recovery.Analysis of definitions of resilience provided by participants resulted in the following synthesis of meaning; being resilient means adopting an attitude of striving to overcome the adversity caused by the experience of schizophrenia. The process of striving enables the person to learn about themselves, the effect of the schizophrenia illness on them, and how to manage it in the context of the life they want to live. Striving to overcome schizophrenia involves struggle, including repeated backwards steps and during this, the individual seeks out and uses supportive people and systems. Having then learned how to overcome and manage the challenges of the schizophrenia illness the individual is then able to apply the same resilient attitude to engage in new challenges and experiences to grow their life in ways unrelated to the illness. Through experiencing the severe adversity of schizophrenia, the person has learned how to be resilient.The presentation will describe the process for becoming resilient with schizophrenia, including factors found to be supportive and factors found to be challenging to the process. An instrument for measuring the resilience of a person diagnosed with schizophrenia is being developed from the research findings.